2019
DOI: 10.1002/hbm.24755
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of co‐altered brain structure and function underlying neurological soft signs in schizophrenia spectrum disorders

Abstract: Neurological soft signs (NSS) comprise a broad range of subtle neurological deficits and are considered to represent external markers of sensorimotor dysfunction frequently found in mental disorders of presumed neurodevelopmental origin. Although NSS frequently occur in schizophrenia spectrum disorders (SSD), specific patterns of co‐altered brain structure and function underlying NSS in SSD have not been investigated so far. It is unclear whether gray matter volume (GMV) alterations or aberrant brain activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 113 publications
2
21
0
Order By: Relevance
“…Schizophrenia is known to affect multiple domains (Fitzsimmons, Kubicki, & Shenton, 2013; Hirjak et al, 2019; Karlsgodt, Sun, & Cannon, 2010) and set up the ground for the initial attempts of multimodal analysis. (Aine et al, 2017; Calhoun & Sui, 2016; Meng et al, 2017; Shile et al, 2016; Sui, Huster, Yu, Segall, & Calhoun, 2014; Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is known to affect multiple domains (Fitzsimmons, Kubicki, & Shenton, 2013; Hirjak et al, 2019; Karlsgodt, Sun, & Cannon, 2010) and set up the ground for the initial attempts of multimodal analysis. (Aine et al, 2017; Calhoun & Sui, 2016; Meng et al, 2017; Shile et al, 2016; Sui, Huster, Yu, Segall, & Calhoun, 2014; Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to their previous findings, Hirjak et al ( 103 ) showed that in addition to the cerebellum, the brainstem and basal ganglia play a role in motor regulation. Moreover, the visuospatial control of motor acts along with the sensorimotor control, as described by the above researchers ( 63 , 101 ), bridges motor and sensory activation—thus supporting Dazzan's introduction of “integrative signs.” The group ( 104 ) even suggested a meaningful integration in terms of a dimensional or brain network approach as being more appropriate to understand motor abnormalities. Thus, they built on Andreasen's cortico-cerebellar-thalamo-cortical circuit (CCTCC) ( 64 ), a hypothetical large network which has influenced schizophrenia research during several decades.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they built on Andreasen's cortico-cerebellar-thalamo-cortical circuit (CCTCC) ( 64 ), a hypothetical large network which has influenced schizophrenia research during several decades. Hirjak et al ( 104 ) supposed that motor function or dysfunction is related to networks which encompass the cerebello-thalamo-cortical, basal ganglia and cortico-motor circuits, as well as serotonergic in addition to dopaminergic neurotransmitters. Correspondingly, the degeneration of the indicated neurotransmitter systems may contribute to age-related fine and gross motor declines, as well as to higher cognitive deficits along with peripheral factors such as a decrease in muscle strength and slowing of movements ( 105 ).…”
Section: Discussionmentioning
confidence: 99%
“… 54 Finally, recent evidence that volume alterations co-occur with aberrant brain activity in cortical and cerebellar systems subserving sensory- and psychomotor organization adds to the concept of sensorimotor dysfunctions as potential biomarkers for psychosis. 14 As such, it is not surprising that motor coordination problems would be associated with more severe manifestations of the disease.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Furthermore, multimodal imaging data have shown that gray matter volume alterations co-occur with aberrant brain activity in cortical and cerebellar systems subserving sensorimotor dynamics and psychomotor organization, pointing to a defined pathophysiological substrate for sensorimotor dysfunctions and contributing to their definition as potential biomarkers for psychosis. 14 …”
Section: Introductionmentioning
confidence: 99%